Halo or Cannibalization? How New Software Entrants Impact Sales of Incumbent Software in Platform Markets - Allen, B.J.; Gretz, Richard T.; Houston, Mark B.; Basuroy, Suman (Journal of Marketing, 2022)
Platform markets involve indirect network effects as two or more sides of a market interact through an intermediary platform. Many platform markets consist of both a platform device and corresponding software. In such markets, new software introductions influence incumbent software sales, and new entrants may directly cannibalize incumbents. However, entrants may also create an indirect halo impact by attracting new platform adopters, who then purchase incumbent software. To measure performance holistically, this article introduces a method to quantify both indirect and direct paths and determine which effect dominates and when. The authors identify relevant moderators from the sensations–familiarity framework and conduct empirical tests with data from the video game industry (1995–2019). Results show that the direct impact often results in cannibalization, which generally increases when the entrant is a superstar or part of a franchise. For the indirect halo impact, superstar entrants significantly increase platform adoption, which can help all incumbents. Combining the direct and indirect impacts, the authors find that only new software that is both a superstar and part of a franchise increases platform adoption sufficiently to overcome direct cannibalization and achieve a net positive effect on incumbent software; all other types of entrants have a neutral or negative overall effect.